A composite cost model for the aeronautical industry: Methodology and case study. (15th September 2015) - Hagnell, M.K.; Åkermo, M.
Abstract: This paper presents a novel composite production cost estimation model. The strength of the model is its modular construction, allowing for easy implementation of different production methods and case studies. The cost model is exemplified by evaluating the costs of a generic aeronautical wing, consisting of skin, stiffeners and rib feet. Several common aeronautical manufacturing methods are studied. For studied structure, hand layup is the most cost-effective method for annual volumes of less than 150 structures per year. For higher production volumes automatic tape layup (ATL) followed by hot drape forming (HDF) is the most cost-effective choice.